2008
DOI: 10.1002/chem.200701960
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Resolution, and Absolute Configuration of Difunctionalized Tröger's Base Derivatives

Abstract: Two racemic derivatives of Tröger's base, the 2,8-diboronic acid ester 6 and the 3,9-dibromo-substituted derivative 5, were synthesized and successfully resolved by HPLC on a chiral stationary Whelk-01 phase on a semipreparative scale, thereby giving rise to both enantiomers in a pure form. These functionalized C(2)-symmetric building blocks are valuable precursors for a variety of further applications. Their absolute configurations were determined by comparison of their quantum chemically calculated CD and UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 55 publications
(41 reference statements)
3
31
0
Order By: Relevance
“…On the one hand, Kostyanovsky and co-workers have confirmed by XRD data a correlation between the absolute configuration of three variously substituted Trçgers base analogues and the sign of the lowest-energy Cotton effect in their CD spectra [60]. On the other hand, Lützen and co-workers have clearly shown that the sign and the magnitude of different Cotton effects may change greatly between various Trçgers base analogues, rendering direct comparison of CD spectra unreliable [59]. Therefore, particular caution is advised in comparing CD spectra of Trçgers base analogues having different substitution patterns of the aromatic rings.…”
Section: Another Interesting Aspect Of Nchmentioning
confidence: 90%
See 1 more Smart Citation
“…On the one hand, Kostyanovsky and co-workers have confirmed by XRD data a correlation between the absolute configuration of three variously substituted Trçgers base analogues and the sign of the lowest-energy Cotton effect in their CD spectra [60]. On the other hand, Lützen and co-workers have clearly shown that the sign and the magnitude of different Cotton effects may change greatly between various Trçgers base analogues, rendering direct comparison of CD spectra unreliable [59]. Therefore, particular caution is advised in comparing CD spectra of Trçgers base analogues having different substitution patterns of the aromatic rings.…”
Section: Another Interesting Aspect Of Nchmentioning
confidence: 90%
“…In addition, the stability of Trçgers base analogues towards racemization in acidic medium considerably depends on the substitution pattern of the aromatic rings. Nonetheless, crystallization of diastereoisomeric salts appears to be of limited scope as enantiomer-separation method, taking into account reports on unsuccessful attempts to resolve Trçgers base analogues with the aid of chiral acids [59].…”
Section: Another Interesting Aspect Of Nchmentioning
confidence: 99%
“…Nonetheless, there are a few examples, such as those of knipholone anthrone (5) or xylogranatin F (6), for which TDDFT calculations are not sufficient to reproduce the ex- Figure 9. Further selected examples of structurally diverse compounds with different types of stereogenic elements, the absolute configurations of which were established by quantum chemical CD calculations (saludimerin A, [83] ancistrotanzanin A, [84] bi [10]paracyclophanes, [56] joziknipholone A, [85] γ-rubromycin, [86] a Tröger's base derivative, [87] resistoflavin, [88] shearinine D, [89] nigerone; [90] for other examples see ref. [91] ).…”
Section: Conclusion: Semiempirical Methods Dft or Mrci?mentioning
confidence: 99%
“…1) have attracted considerable attention for their properties and reactivities. [41][42][43][44][45][46][47][48][49] Many different types of Tröger bases have been prepared thanks to very modular synthetic routes to the tricyclic core, [50][51][52][53][54][55][56][57][58] and this for a variety of applications such as molecular recognition, 59-61 DNAinteracting probes, 62 biomimetic systems, 63 self-assembled structures, 64,65 or as analytes for chiral stationary phase chromatography. [66][67][68][69][70][71][72] However, in terms of stereochemistry, these compounds undergo relatively facile racemization in acidic media with moderate barriers of inversion (ca.…”
Section: Synthesis Of N-phenylacetyl Tröger Basementioning
confidence: 99%